2013
DOI: 10.1111/jphp.12038
|View full text |Cite
|
Sign up to set email alerts
|

Role of gastric mucus secretion, oxinitrergic system and sulfhydryl groups on the gastroprotection elicited by Polygala cyparissias (Polygalaceae) in mice

Abstract: The data suggested that PCAE and PCMF displayed antiulcer activity due to different mechanisms and with the participation of phenolic compounds obtained from the plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Astragalin, a pharmacologically active flavonoid isolated from C. cyparissias , has been examined for its antiulcer activity. Results demonstrated that 30 mg/kg dosage of astragalin effectively decreases percentage of lesion area, total area of lesion, and ulcer index in the mice model of gastric secretion [ 97 ].…”
Section: Biological Activities Of Astragalin and Their Mechanisms mentioning
confidence: 99%
“…Astragalin, a pharmacologically active flavonoid isolated from C. cyparissias , has been examined for its antiulcer activity. Results demonstrated that 30 mg/kg dosage of astragalin effectively decreases percentage of lesion area, total area of lesion, and ulcer index in the mice model of gastric secretion [ 97 ].…”
Section: Biological Activities Of Astragalin and Their Mechanisms mentioning
confidence: 99%
“…It is known that nitric oxide (NO) plays an important role in the defense of the gastric mucosa and is a biological mediator which regulates the secretion of mucus and blood flow (Falcao Hde et al, 2013). In the gastrointestinal tract, NO is also involved in modulating the activity of mast cells together with endogenous prostaglandins (Klein-Junior et al, 2013;Wallace, 2006). Our results showed that the inhibition of NO synthase by L-NAME did not reverse gastroprotection effect of AFHP, thereby suggesting that NO synthesis is not critical to its gastroprotective activity.…”
Section: Discussionmentioning
confidence: 60%
“…There was variability in the study regions for the selected manuscripts, with 25% of the papers coming from Asia ( Moon et al, 2011 ; Asha et al, 2013 ; Manayi et al, 2013 ; Wang et al, 2014 ; Park et al, 2016 ; Ibrahim et al, 2018 ; Kim et al, 2018 ; Lu et al, 2018 ; Saravanakumar et al, 2019 ; Ma X. et al, 2020 ; Das et al, 2020 ), 56.82% from America, of which 40.91% were from South America ( Adzu et al, 2015 ; Almeida et al, 2019 ; Arunachalam et al, 2019 ; Borges et al, 2020 ; da Silva Junior et al, 2016 ; de Cássia dos Santos et al, 2019 ; Garro et al, 2015 ; Klein-Júnior et al, 2013 ; Marcial et al, 2014 ; Mazzolin et al, 2010 ; Minozzo et al, 2016 ; Miranda et al, 2015 ; Mota Da Silva et al, 2015 ; Oliveira et al, 2015 ; Pastene et al, 2014 ; Ribeiro et al, 2013 ; Santos et al, 2012 ; Spósito et al, 2019 ) and 15.91% from North America ( Ankolekar et al, 2011 ; Brown and Jiang, 2013 ; Escobedo Hinojosa et al, 2014 ; Palacios-Espinosa et al, 2014 ; Espinosa-Rivero et al, 2015 ; Egas et al, 2018 ; Gomez-Chang et al, 2018 ), 9.09% of the articles originated from the Africa ( Okeleye et al, 2011 ; Lawal et al, 2014 ; Hamad et al, 2015 ; Fahmy et al, 2020 ), and 9,09% from the Europe ( Bisignano et al, 2013 ; Cardoso et al, 2018 ; Zengin et al, 2018 ; Cesa et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%